Formulasi Gel Antijerawat dari Ekstrak Etil Asetat Gambir - Anggraini, Deni; Rahmawati, Noveri; Hafsah, Siti (Jurnal Penelitian Farmasi Indonesia, 2013)
The formulas of antiacne gel preparation of ethyl acetate extract of gambir have been formulated by using carbopol 940P as its bases. In thisstudy, five difference gel formulas F1, F2, F3, F4 and F5, were prepared with 0.5; 1; 2; 4 and 6% of concentration of extract, respectively.The result showed that organoleptic of al formulas was found unstable, while the appearance of gel F1 and F2 were homogeneous and stableat room temperature as well as cooling process. In addition, all formulas exhibited stable value in pH evaluation and did not irritate the skin.